On page 62 of his book “General Relativity”, Robert Wald writes the stress-energy tensor $T_{ab}$ for a perfect fluid in the form

$$T_{ab} = \rho u_au_b + P(\eta_{ab} + u_au_b), \tag{1}$$

and then says that the equation of motion, when the fluid is not subject to external forces, is

$$\partial^a T_{ab}=0. \tag{2}$$

He projects this equation parallel and perpendicular to $u_b$ to find

$$u^a\partial_a\rho + (\rho + P)\partial^au_a = 0, \tag{3}$$ $$(P +\rho) u^a\partial_a u_b + (\eta_{ab} + u_au_b)\partial^a P = 0. \tag{4}$$

I see that if I multiply equation $(3)$ by $u_b$ and add it to equation $(4)$, I obtain equation $(2)$, but why is the term $u_au_b \partial^a P$ in equation $(4)$ (the one perpendicular to $u_b$) and not in equation $(3)$ as $u_a\partial^aP$?


1 Answer 1


I think the issue you’re having is that you didn’t use the contraction $u_bu^b=-1$ along the way. Anyway, below is the full answer.

In general, if you’re given a unit timelike vector (i.e a vector $u$ such that $g(u,u)=-1$), then the orthogonal projection of a vector $\xi$ onto the subspace spanned by $u$ is $P_{\parallel}(\xi)=-g(\xi,u)u$. A similar statement holds for covectors.

In index notation, if $u_au^b=-1$, then the projection of $\xi^a$ onto $u^b$ is $-(\xi_au^a)u^b$, where index raising and lowering is done with $g_{ab}$. The covector version is of course that the projection of $\xi_a$ onto $u_b$ is $-(\xi_au^a)u_b$.

Ok, so now coming to the stress energy tensor, let’s write it as $T_{ab}=(\rho+P)u_au_b+Pg_{ab}$, and let’s define $\xi$ to be the divergence: \begin{align} \xi_b&=\nabla^a(T_{ab})\\ &=\nabla^a(\rho+P)\,u_au_b+(\rho+P)(\nabla^au_a)u_b+(\rho+P)u_a(\nabla^au_b)+(\nabla^aP)g_{ab}+\underbrace{P\nabla^ag_{ab}}_{=0} \end{align} where I have used metric compatibility to say the last term vanishes. Now, as mentioned above, the projection onto $u$ is $-(\xi_au^a)u_b$, but since $\xi_b=0$ (the stress tensor is divergence free) this (co)vector equation is equivalent to the scalar equation $\xi_bu^b=0$. We can easily evaluate $\xi_bu^b$ using the above formula and the normalization condition $u_bu^b=-1$: \begin{align} 0&=\nabla^a(\rho+P)\,u_a\cdot (-1)+(\rho+P)(\nabla^au_a)\cdot (-1)+(\rho+P)u_a(\nabla^au_b)u^b+\underbrace{(\nabla^aP)g_{ab}u^b}_{=(\nabla^aP)u_a}\\ &=-(\nabla^a\rho)u_a-(\rho+P)(\nabla^au_a)+(\rho+P)u_a(\nabla^au_b)u^b, \end{align} where I have cancelled the term $(\nabla^aP)u_a$ which appears twice with opposite sign. Lastly, this third term vanishes by differentiating the normalization condition $u_bu^b=-1$ (in index-free notation, $g(u,u)=-1$ so applying $\nabla_u$ to both sides and using metric compatibility, and symmetry of $g$, we get $2g(\nabla_uu,u)=0$). Thus, we end up with the equation \begin{align} 0&=-\xi_bu^b=(\nabla^a\rho)u_a+(\rho+P)(\nabla^au_a), \end{align} which is your equation (3).

To get the perpendicular component, you simply look at $\xi_b+(\xi_au^a)u_b$, which simplifies to \begin{align} 0&=\xi_b+(\xi_au^a)u_b\\ &=\xi_b-\left[(\nabla^a\rho)u_a+(\rho+P)(\nabla^au_a)\right]u_b\\ &=(\nabla^aP)u_au_b+(\rho+P)u_a(\nabla^au_b)+(\nabla^aP)g_{ab}\\ &=(\rho+P)u_a(\nabla^au_b)+(g_{ab}+u_au_b)\nabla^aP, \end{align} which gives you equation (4).

  • $\begingroup$ if you want to, you can replace $g_{ab}$ with $\eta_{ab}$ and all covariant derivatives with partial derivatives, but since Wald introduces the necessary differential geometry early on in the book, I figured why not just prove the more general version, since it’s not much more effort anyway. $\endgroup$
    – peek-a-boo
    Jun 12, 2023 at 23:58

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.